A study on the relationship between reading motivation and reading strategies used by UiTM students in Dungun, Terengganu / Badariah Sani, Muhmad Noor Wan Chik and Yah Awang Nik - Sani, Badariah; Wan Chik, Muhmad Noor; Awang Nik, Yah (2006)
Reading motivation is considered as the most important motivational construct that influence achievement behaviour. The researchers in this study investigated the relationship between reading motivation and reading strategies used by Part 2 students in UiTM Terengganu. 245 students from five different programs were chosen as samples A 45 item questionnaire was adapted from “Motivation for Reading Questionnaire” by Wigfield and Guthrie was used. The eleven dimensions of reading motivation was measured and the results showed the students having a moderate score for reading motivation. The correlation between the two variables also showed a moderate score. However the t statistic’s results revealed that there was no significant between the two variables. The researchers contend that the students’ reading motivation has no influence on the acquisition of reading skills and that these skills are acquired through teacher modeling and students practicing the skills. Suggestions on improving reading motivation and reading strategies were given.